Answer:
0 (zero)
Step-by-step explanation:
![{x}^{2} y - y + x {y}^{2} - x \\ = {4}^{2} \times 0.25 - 0.25 + 4 \times {0.25}^{2} - 4 \\ = 16 \times 0.25 - 0.25 + 4 \times 0.0625- 4 \\ = 4 - 0.25 + 0.25 - 4 \\ = 0 \\ \\ \purple {\boxed{ \bold{ \therefore \: {x}^{2} y - y + x {y}^{2} - x = 0}}}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20y%20-%20y%20%2B%20x%20%7By%7D%5E%7B2%7D%20%20-%20x%20%20%5C%5C%20%20%3D%20%20%7B4%7D%5E%7B2%7D%20%5Ctimes%20%200.25%20-%200.25%20%2B%204%20%5Ctimes%20%20%7B0.25%7D%5E%7B2%7D%20%20-%204%20%5C%5C%20%20%3D%2016%20%5Ctimes%20%200.25%20-%200.25%20%2B%204%20%5Ctimes%20%200.0625-%204%20%20%5C%5C%20%20%3D%204%20-%200.25%20%2B%200.25%20-%204%20%5C%5C%20%20%3D%200%20%5C%5C%20%20%5C%5C%20%20%5Cpurple%20%7B%5Cboxed%7B%20%5Cbold%7B%20%5Ctherefore%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20y%20-%20y%20%2B%20x%20%7By%7D%5E%7B2%7D%20%20-%20x%20%20%3D%200%7D%7D%7D)
Answer:
y=-4/7
Step-by-step explanation:
7y/2=-2
multiply both sides by 2
7y=-4
divide both sides by 7
y=-4/7
Answer:
8.2
Step-by-step explanation:
let me know if its wrong
Average rate of change: r=[f(b)-f(a)]/(b-a)
r=-60→[f(b)-f(a)]/(b-a)=-60
b=5; f(b)=-213; a=1; f(a)=27
(-213-27)/(5-1)=(-240)/4=-60
Answer: The <span>two points in the table which create an interval with an average rate of change of -60 are:
x f(x)
1 27
5 -213</span>
Answer:
<h2>
1 31/104</h2>
Step-by-step explanation:
First, let's turn them both into improper fractions.
3 3/8 = 27/8
Now we can multiply
It is 5*27 / 13 * 8
This equals: 135 / 104
Simplified even further is:
1 31/104